1996
DOI: 10.1074/jbc.271.44.27723
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated Protein Kinase Phosphorylates Cytosolic Phospholipase A2 (cPLA2) in Thrombin-stimulated Platelets

Abstract: The Ca 2؉ -sensitive 85-kDa cytosolic phospholipase A 2 (cPLA 2 ) is responsible for thrombin-stimulated mobilization of arachidonic acid for the synthesis of thromboxane A 2 in human platelets. We have previously shown that thrombin activates p38 kinase, a recently discovered new member of the mitogen-activated protein kinase family (Kramer, R. M., Roberts, E. F., Strifler, B. A., and Johnstone, E. M. (1995) J. Biol. Chem. 270, 27395-27398) and also induces phosphorylation of cPLA 2 , thereby increasing its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(180 citation statements)
references
References 37 publications
6
168
1
2
Order By: Relevance
“…Interestingly, it has been reported that, in human platelets, p38 MAP kinase could phosphorylate and activate cPLA 2 after stimulation with thrombin and collagen (9,32). Furthermore, stress-inducing stimuli such as H 2 O 2 increased the phosphorylation and activation of cPLA 2 and enhanced Ca 2ϩ ionophore-induced arachidonic acid release, both of which were prevented by p38 MAP kinase inhibitor but not by ERK inhibitor in human platelets (10).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, it has been reported that, in human platelets, p38 MAP kinase could phosphorylate and activate cPLA 2 after stimulation with thrombin and collagen (9,32). Furthermore, stress-inducing stimuli such as H 2 O 2 increased the phosphorylation and activation of cPLA 2 and enhanced Ca 2ϩ ionophore-induced arachidonic acid release, both of which were prevented by p38 MAP kinase inhibitor but not by ERK inhibitor in human platelets (10).…”
Section: Discussionmentioning
confidence: 98%
“…p38 MAP kinase, which plays a role in the stress-stimulated signal transduction pathway, has been reported to serve as an activator for cPLA 2 via its phosphorylation in thrombin-or collagen-stimulated platelets (9,32). Therefore, we examined the contribution of p38 MAP kinase to cPLA 2 activation and to arachidonic acid release under the experimental conditions used here.…”
Section: Resultsmentioning
confidence: 99%
“…p38 activation also upregulates glucose transport (Barros et al 1997). The p38 MAP kinase has also been shown to be activated by other stimuli, including bradykinin, which leads to an inhibition of N-type voltage-dependent Ca¥ currents (VDCCs; Wilk-Blaszczak et al 1998), thrombin, which leads to activation of cPLA2 (Kramer et al 1996), â_amyloid fibrils (McDonald et al 1998) and glutamate in cerebellar neurones, which leads to apoptosis (Kawasaki et al 1997).…”
Section: Effects Of Il_1â On Synaptic Transmissionmentioning
confidence: 99%
“…Peptide arrays were synthesized on cellulose membrane using a MultiPep automated peptide synthesizer (INTAVIS Bioanalytical Instruments AG) as described previously (Kramer et al, 1996). Interaction analyses between peptide and recombinant protein were probed by overlaying the membranes with recombinant protein, and bound proteins were detected with HRP-conjugated anti-GST antibody (clone RPN1236; GE Healthcare).…”
Section: Peptide Array Overlay Assaymentioning
confidence: 99%